2016
DOI: 10.5099/aj160200169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Garlic Extract (Allium Sativum) on Lipid Profile of Wister Rats

Abstract: Lipid profile in Wister rats was investigated after administration of different concentration of aqueous extract of Allium sativum. The animals were divided into five (5) groups of five rats in each group, and were given different concentrations of the extract for three weeks. Thereafter, plasma lipid profiles were assayed. The result of comparing the mean total cholesterol (T. CHOL), triglyceride (TG), Low density lipoprotein (LDL) and control levels with those of the test groups A, B, C and D showed great de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Garlic ( Allium sativum L.) belongs to the family Liliaceae is a perennial bulb forming plant has been widely used in dietary and medicinal purpose from the ancient time [ 30 ]. It has been reported that its decomposition product diallyl disulfide, diallyl trisulfide are well known for their antihyperlipidemic properties and another compound allicin is responsible for lowering serum cholesterol level [ 31 ]. From ancient time garlic has been a cure for heart disease, headache, cancer and management of cholesterol [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Garlic ( Allium sativum L.) belongs to the family Liliaceae is a perennial bulb forming plant has been widely used in dietary and medicinal purpose from the ancient time [ 30 ]. It has been reported that its decomposition product diallyl disulfide, diallyl trisulfide are well known for their antihyperlipidemic properties and another compound allicin is responsible for lowering serum cholesterol level [ 31 ]. From ancient time garlic has been a cure for heart disease, headache, cancer and management of cholesterol [ 32 ].…”
Section: Introductionmentioning
confidence: 99%